О заселении иксодовыми клещами лесов поймы Нижнего и Среднего Амура - Савицкий, Б.П.; Савицкая, Г.М. (Вестник зоологии, 1976)
Inhabiting the Amur flood plain by the Ixodoidea superfamily starts at the aging stage of primary osieries. The inhabitance results from their transfer by the domestic host animals. The pasture species, Haemaphysalis concinna K o c h. and Dermacentor silvarum 0 1., are the first to inhabit the flood plain. As the coniferous and broad-leaved forest species penetrate into the flood plain there appear two more distributed in the Amur area species of the mites Ixodes persulcatus P. S c h. and Haemaphysalis japonica douglasi N u t. et W a r b. as well as Ixodes angustus N e u m. They are transferred not only by domestic, but also by inhabiting wild animals.